Psychological Distance and the Dual Role of Price - Bornemann, Torsten; Homburg, Christian (Journal of Consumer Research, 2011)
Abstract When evaluating a product, consumers may interpret price information as either an indicator of quality or an indicator of monetary sacrifice. On the basis of construal level theory, we propose that psychological distance alters the weight consumers attach to these opposing roles of price. Four experiments show (1) that from both a temporally and a socially distant perspective, the price–perceived quality relationship is more pronounced; (2) that from a temporally proximal perspective, the price–perceived sacrifice relationship is more pronounced; (3) that these effects stem from differences in the way consumers mentally construe price information; and (4) that when people initially use price to judge a product for distant future consumption, it receives less attention as an indicator of sacrifice in a later evaluation for near future consumption. These findings have implications for prelaunch communication activities and preference elicitation methods such as conjoint analysis.